2018
DOI: 10.1029/2018tc005209
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Anisotropy and Its Geodynamic Implications in Iran, the Easternmost Part of the Tethyan Belt

Abstract: In this study, we use the results of seismic anisotropy as inferred from shear wave splitting analyses of SKS phases to propose a geodynamical model of the Arabia‐Eurasia collision zone. A detailed analysis of the 202 non‐null splitting and 196 null splitting measurements obtained from a dense temporary network are utilized to investigate the possibility of lateral and vertical variations in the anisotropic parameters and the hypothesis of a dipping anisotropic layer. A 2‐D geodynamical model of the western pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…In Fig. 2 , we also present the results of previous studies (yellow bars) 12 , 13 . We do not explicitly show earlier results of Kaviani et al 11 and Rahimzadeh et al 14 , since we have re-processed and updated the data at the corresponding stations.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…In Fig. 2 , we also present the results of previous studies (yellow bars) 12 , 13 . We do not explicitly show earlier results of Kaviani et al 11 and Rahimzadeh et al 14 , since we have re-processed and updated the data at the corresponding stations.…”
Section: Resultsmentioning
confidence: 61%
“…In a previous study, Kaviani et al 11 investigated azimuthal anisotropy beneath the Zagros and Iranian Plateau; however, the limited station coverage and short observational time frame did not allow for a detailed investigation of the entire region. Sadeghi-Bagherabadi et al 12 , 13 presented the results of shear-wave splitting (SWS) analysis from a temporary profile of stations across the NW Zagros, NW central Iran and Alborz. These studies show small-scale variations in anisotropic structure along the profile; however, it is difficult to generalize the conclusions deduced from these limited observations to the entire Zagros and the Iranian Plateau.…”
Section: Introductionmentioning
confidence: 99%
“…At present, lacking an integrated velocity model of both SH‐wave and SV‐wave velocities in the study region makes it hard to ascertain the contribution of radial anisotropy to the observed discontinuities, and the poor back‐azimuth coverage of the S‐RF data used impedes a thorough analysis of azimuthal anisotropy. On the other hand, the re‐analyses (Priestley et al., 2012; Sadeghi‐Bagherabadi et al., 2018a) of SKS‐splitting measurements (Kaviani et al., 2009; Sadeghi‐Bagherabadi et al., 2018b) pose an anisotropic source in the asthenosphere beneath Central Iran possibly induced by vigorous mantle convection. It therefore suggests that a contribution from anisotropy to the LAB or PVD may not be easily excluded without further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…According to them the agreement between the observed directions of anisotropy with the direction of maximum shear as inferred from geodetic measurements implies a vertically coherent deformation within the lithosphere of Iran. Sadeghi-Bagherabadi et al 2018a, 2018b examined the shear wave splitting of the SK(K)S phases along a seismic array in western Iran across the collision zone from the Zagros to the Alborz. Their work revealed that while in the Zagros, the thick lithospheric root accounts for the along-strike fast polarization directions, in central Iran and the Alborz, the asthenospheric mantle flow field in the far-field away from the collisional front is responsible for the observed fast directions, which trend subparallel to the absolute plate motion (APM) vectors.…”
Section: R E G I O N a L T E C T O N I C S E T T I N G A N D P R E V I O U S A N I S O T Ro P Y S T U D I E Smentioning
confidence: 99%
“…1) and showed a complicated pattern of fast axes where they repeatedly change from range-perpendicular to range-subparallel. Based on this observed variability, Sadeghi-Bagherabadi et al (2018b) put forward the alternative interpretation that the observed anisotropy over central Iran mostly reflects the pattern of an asthenospheric flow field beneath a thin lithosphere affected by the keel of a thick Zagros lithosphere and an edge-driven small-scale convective flow in the region of strong lithospheric thickness gradient. Specifically, they partially attributed the NW-SE fast orientations along the NW margin of central Iran (coincident with our study area) to toroidal convective flow, which establishes a horizontal component normal to the lithospheric gradient (Kaislaniemi & van Hunen 2014).…”
Section: Geodynamic Interpretation and Comparison With Previous Studiesmentioning
confidence: 99%